1998
DOI: 10.1074/jbc.273.32.20636
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen-activated Protein Kinase Mediates the Transcriptional Induction of the Atrial Natriuretic Factor Gene through a Serum Response Element

Abstract: In various cell types certain stresses can stimulate p38 mitogen-activated protein kinase (p38 MAPK), leading to the transcriptional activation of genes that contribute to appropriate compensatory responses. In this report the mechanism of p38-activated transcription was studied in cardiac myocytes where this MAPK is a key regulator of the cell growth and the cardiac-specific gene induction that occurs in response to potentially stressful stimuli. In the cardiac atrial natriuretic factor (ANF) gene, a promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
100
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 39 publications
5
100
1
Order By: Relevance
“…Luciferase reporter plasmids with the promoter sequences of cardiac ␣-actin, SM22, atrial natriuretic factor, c-jun (JC6), and 5ϫGAL4-E1B-luc were as described (41)(42)(43)(44). The human smooth muscle ␣-actin luciferase reporter was a gift of C. Chandra Kumar.…”
Section: Methodsmentioning
confidence: 99%
“…Luciferase reporter plasmids with the promoter sequences of cardiac ␣-actin, SM22, atrial natriuretic factor, c-jun (JC6), and 5ϫGAL4-E1B-luc were as described (41)(42)(43)(44). The human smooth muscle ␣-actin luciferase reporter was a gift of C. Chandra Kumar.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, sub- cellular fractionation and immunoblotting were used to examine the effects of sI and sI/R on ATF6 processing and translocation in cultured cardiac myocytes. There are two forms of ATF6; ATF6␣ and ATF6␤ are both cleaved during ER stress, and the N-terminal fragments translocate to the nucleus, where they bind to ERSEs and influence ER stress response gene expression (28,30,52,53). However, upon activation, ATF6␣ is extremely labile, making it difficult to detect after cleavage and translocation, whereas ATF6␤ is much more stable (23,40).…”
Section: Figure 3 Effect Of Si/r On Grp78-luciferasementioning
confidence: 99%
“…Recent studies have demonstrated that the N-terminal domain of ATF6 is responsible for transcriptional activation when fused to a heterologous DNA-binding domain (11), whereas the central region of ATF6 possesses a b-Zip domain that is characteristic of some DNA-binding proteins. It has been shown in HeLa cells that full-length ATF6, composed of 670 amino acids, resides in the ER membrane; the region of ATF6 responsible for anchoring it in the ER membrane is located in the approximate center of the protein, between amino acids 378 and 398 ( Fig.…”
mentioning
confidence: 99%